The Effect of Rewards Towards Employees Motivation at Anjasmoro Adventist Academy - Reymand M. Hutabarat; Francis M. Hutabarat (Jurnal Koinonia, 2013)
This study examines the effect of rewards and employee’s work motivation at Anjasmoro Adventist Academy. Employees here are taken as sample of the study. The study is descriptive and a quantitative methodology was used for the study and questionnaire was used as the method of measuring instrument. The four independent variables of reward included, payment, promotion, recognition, benefits and the dependent variable was employee work motivation. The data was analyzed using the techniques of rank correlation coefficient and regression analysis. All the findings were tested at 0.05 level of significance. The result concludes that there is a positive and significant relationship between rewards and the employee’s work motivation.